2008
DOI: 10.1175/2008jcli2296.1
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into North European and North Atlantic Surface Pressure Variability, Storminess, and Related Climatic Change since 1830

Abstract: The authors present initial results of a new pan-European and international storminess since 1800 as interpreted from European and North Atlantic barometric pressure variability (SENABAR) project. This first stage analyzes results of a new daily pressure variability index, dp(abs)24, from long-running meteorological stations in Denmark, the Faroe Islands, Greenland, Iceland, the United Kingdom, and Ireland, some with data from as far back as the 1830s. It is shown that dp(abs)24 is significantly related to win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 43 publications
4
60
2
Order By: Relevance
“…Despite the fact that surges measure changes in wind speed and direction, the analysis of high annual percentiles of surges at Cuxhaven confirms earlier observational studies on storminess over the European-Atlantic region with conventional proxies (Schmidt and von Storch 1993;Alexandersson et al 1998Alexandersson et al , 2000B€ arring and von Storch 2004;Matulla et al 2008;Hanna et al 2008;Wang et al 2009) in terms of both variability and trends. Consistent with the different pressure-based storm indices of the last up to 150 yr, periods of increased storminess with higher occurrence of extreme storm surges prevailed at the end of the nineteenth and twentieth century, with very low levels in the 1970s.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Despite the fact that surges measure changes in wind speed and direction, the analysis of high annual percentiles of surges at Cuxhaven confirms earlier observational studies on storminess over the European-Atlantic region with conventional proxies (Schmidt and von Storch 1993;Alexandersson et al 1998Alexandersson et al , 2000B€ arring and von Storch 2004;Matulla et al 2008;Hanna et al 2008;Wang et al 2009) in terms of both variability and trends. Consistent with the different pressure-based storm indices of the last up to 150 yr, periods of increased storminess with higher occurrence of extreme storm surges prevailed at the end of the nineteenth and twentieth century, with very low levels in the 1970s.…”
Section: Discussionsupporting
confidence: 78%
“…Hence, the scientific community proceeded to the evaluation of more homogeneous storminess proxies, which have been observed over longer time periods. Typical examples for such proxies are storm indices calculated from single station pressure readings (e.g., B€ arring and von Storch 2004; Hanna et al 2008), high annual percentiles of geostrophic winds derived through * Supplemental information related to this paper is available at the Journals Online website: http://dx.doi.org/10.1175/JCLI-D-13-00427.s1. triangulation of pressure readings (Schmidt and von Storch 1993;Alexandersson et al 1998Alexandersson et al , 2000, or storm surge records from tide gauge measurements (von Storch and Reichardt 1997;Zhang et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Based on different storm indices derived from singlestation pressure readings for Lund and Stockholm, Bärring and von Storch (2004) and Bärring and Fortuniak (2009) found no robust signs of any long-term trend in southern Sweden for the period 1780/1800 to 2005. Hanna et al (2008) found similar results based on a daily pressure variability index calculated as absolute 24 h pressure differences, that is Dp = |p t+24 − p t+0 |, for the British Isles since 1830 and for Denmark since 1874 confirming increased storminess at the end of the nineteenth century and the 1980s to 1990s, with the 1880s being the stormiest decade. The informational value of five different pressure-based storminess indices including those used by Bärring and von Storch (2004) and Hanna et al (2008) was evaluated by Krueger and von Storch (2012).…”
Section: Long-term Wind Climatesupporting
confidence: 69%
“…Hanna et al (2008) found similar results based on a daily pressure variability index calculated as absolute 24 h pressure differences, that is Dp = |p t+24 − p t+0 |, for the British Isles since 1830 and for Denmark since 1874 confirming increased storminess at the end of the nineteenth century and the 1980s to 1990s, with the 1880s being the stormiest decade. The informational value of five different pressure-based storminess indices including those used by Bärring and von Storch (2004) and Hanna et al (2008) was evaluated by Krueger and von Storch (2012). The authors confirmed the general usefulness of the indices as storminess proxies, with absolute pressure tendencies per six or eight hours containing the highest informational value.…”
Section: Long-term Wind Climatesupporting
confidence: 69%
“…The North Atlantic experienced increased cyclonic activity with increased storminess from the early 1960s until the mid nineties after a relatively quiescent period from about 1930 (Hanna et al, 2008). The climatic stability and therefore the justification for using an index parameter extracted from the last 100 years of observations is an open question.…”
Section: Introductionmentioning
confidence: 99%